HISTORY OF NOURISHMENT IN SOUTHERN EUROPE: THE CASE OF PRISONERS IN LOULÉ (19th CENTURY) - Guerreiro Martins, Luísa Fernanda (Journal of Tourism, Sustainability and Well-being, 2018)
In this paper we use data collected from historical documentation to contribute to a better understanding of the quality of nourishment in southern Europe, in particular, in the Portuguese Algarve. We analyse the typology of the food provided to the prisoners, considering that strong budget constrains in prisons. Also, a trial to understand whether this typology corresponds to an appropriate example of the Mediterranean Diet framework or not. In general terms, the way how people living in the ancient town of Loulé were nourished, during the last years of the 19th century and the first years of the 20th century, is known due to the studies developed by hygienist Geraldino Brites in 1911 and published in 1914. But we did not know what prisoners in jail used to eat daily, or who was responsible for their nourishment, until we read the documentary collection concerning the prison of Loulé which is deposited in the Municipal Archive of Loulé. Because studies providing information on the system prevailing in prisons are rare, our study offers precious information related to dietary priorities and food awareness related nourishment of the prisoners, or situations of strong budgetary restrictions.